Perlindungan Hak Paten: Perspektif Hukum Nasional dan Hukum Islam - Syarifah Rara Warda Nyrvana; Romi Faslah (CV. ITTC INDONESIA, 2025)
This article discusses the concept and legal framework of patent rights from both Indonesian national law and Islamic legal perspectives. As intellectual property becomes increasingly crucial in the era of innovation and globalization, patent protection plays a strategic role in ensuring the rights of inventors. The study uses a normative juridical approach by analyzing primary legal sources such as the Patent Law No. 13 of 2016, TRIPs Agreement, and classical as well as contemporary Islamic legal thought. It also presents a case study involving PT Kalbe Farma and PT Hexpharm Jaya to examine how patent disputes are resolved in practice. The analysis reveals that both national and Islamic legal systems recognize patent rights as a form of protected ownership. However, both also emphasize public interest by allowing exceptions like compulsory licensing. Therefore, patent protection must be balanced between individual rights and public benefit.